The Culture and Age of First Marriage on Female Teenagers in West Marawola (Medico Legal Update, 2020)
Age of First Marriage is the age at which a person is legally and biologically married for the first time. According to UNICEF, the percentage of women who decide to get child marriage in the world throughout 2016 is 12 million. Southeast Asia and Asia-Pacific are the highest in the number of child marriage. In Southeast Asia, Indonesia ranks second highest for child marriage. The purpose of the study was to determine the factors associated with the age of first marriage in young women in West Marawola Sub-District. This research was categorized as quantitative research with cross-sectional approach. The population was young women aged 10-24 in the West Marawola Sub-District with a percentage of 988 people taken as the sample (Proportionate Stratified Random Sampling). The analysis was conducted using univariate and bivariate analysis at a confidence level of 95% (). The chi-square test results showed that Knowledge (=0,001), Parental Support (=0,000), Culture (=0,040), and Family Planning Instructor (=0,037) are related to the Age of First Marriage. It is expected that this research is able to socialize the age of marriage, so that young women can delay their marriage.